Improving Network Security: Blockchain-based Authentication and Authorization Scheme in Accordance with Weighted Nodes in a Clustered Network - Bushra Mohammed Jawad; Saif Mahmood Al-alak (Iraqi Journal for Computers and Informatics)
ABSTRACT Addressing concerns related to network security involves protecting a network from various threats, including internal and external risks, such as identity theft, collusion, malicious activities, and other attacks. This study aims to address these challenges by introducing the authentication of the identity of nodes that are connected to a network, utilizing blockchain technology and consensus algorithms as integral elements of its security framework. To improve security and deal with identity theft and spoofing attacks in clustered networks, we suggest implementing a blockchain-based authentication and authorization scheme. This scheme ensures that the authentication of nodes or devices relies on blockchain technology, employing a voting algorithm to validate the eligibility of nodes that are seeking access to a network. A new block is generated for each incoming node, and this block contains essential information about that node. The decision to accept a new node into the network is determined through a voting process that considers individual node weights calculated based on three key factors: initial weight, age, and incentive. Java NetBeans IDE 8.0.2 is used to design and implement the simulator. Experimental results comprise the implementation of consensus algorithms and demonstrate the effect of the highest weight nodes. Moreover, these algorithms will launch attacks on the network and are aware of our scheme’s ability to detect such attacks. The simulation results show that our authentication scheme exhibits advantages in terms of security, scalability, and resistance capability against attacks.